Promoting ethical follower behaviour through leadership of ethics: The development of the ethical leadership inventory (ELI) - H. Spangenberg; C. C. Theron (South African Journal of Business Management, 2005)
The Centre of Leadership Studies developed a model that defines and describes leadership behaviour required for creating an ethical and high performing organisation. Purposefully building an ethical organisational environment is a prerequisite for ethical organisational behaviour. To be an ethical high performance leader, a person must be both an effective leader and a leader of ethics. The purpose of this study is to develop a 360° instrument that can be used to assess the quality of ethical leadership of middle, senior and executive managers in public, private and not-for-profit organisations. The results reported here provide reasonable support for the use of the ELI. The possibility of causal influences existing amongst specific first-order leadership dimensions, however, needs to be investigated.
Keywords: 650